Perception of Intonation on Neutral Tone in Mandarin - Zhang, Yixin; Schmidt, Elaine; Post, Brechtje (Frontiers in Communication, 2022)
In Mandarin, lexical tone has been found to interact with intonational tone to influence intonation perception, with the falling T4 facilitating the perception of the statement/question contrast the most, and the rising T2 the least. However, in addition to the four citation tones T1-T4, Mandarin has ‘neutral tone’ which marks weak, non-initial syllables that do not carry a citation tone. The prevailing view is that neutral tone is, in fact, phonologically toneless. It is unknown whether neutral tone can also affect intonation perception. However, it is reasonable to hypothesize that if neutral tone is indeed toneless, it cannot interact with intonational tone in the same way as citation tones do. We investigated this novel hypothesis with a perception experiment in which twenty-two Mandarin speakers had to determine whether disyllabic citation tone and neutral tone words were a question or statement. Results show that the identification of intonation contours is more accurate for neutral tone than for T2, and similarly accurate for neutral tone and T4, regardless of whether the neutral tone is underlying or derived. Furthermore, both T4 and neutral tone are realized with a reduced pitch range at a higher pitch level in questions, unlike T2, which is characterized by a slightly expanded pitch range and a higher pitch level. It is possible that intonation perception in Mandarin is facilitated by changes in the phonetic shapes of lexical tones brought by intonation rather than the phonological interaction between lexical tones and intonation. The importance of pitch changes to the intonation perception in Mandarin was further tested in a second perception experiment with the same twenty-two participants and disyllabic stimuli with manipulated pitch level and range. Results indicate that the use of pitch cues in intonation perception shows tone-specific differences, namely, pitch range is more important in signaling the question/statement contrast in utterances ending with T4 or neutral tone, while pitch level is the only perceptual cue to interrogativity for utterances ending in T2.